Role and Authority: An Empirical Study on Internal Auditors in Malaysia - Mahzan, Nurmazilah; Zulkifli, Norhayah; Umor, Sarimah (Asian Journal of Business and Accounting, 2012)
One important relationship between members of the internal audit profession and others in the work world is that of authority because it has the most pervasive direct and indirect influence upon the clarity of the internal auditors’ role. Internal auditors have varying roles among which are control oversight, decision support and risk management. We noted that the lack of authority will affect the internal auditors’ role clarity and hence its effectiveness. The main objective of this paper is to identify the relationship between the roles of the internal auditors and authority. The extent to which the internal auditors enjoy role clarity is determined by how they perceive their roles. This paper provides empirical evidence on the association between internal auditor roles and other aspects of a profession such as audit charter existence and employment type. The results show that although management intimidation is dominant in explaining the variance in authority, this construct only explains 13.7 per cent variance in authority. The results support the need for the regulators, the professional body which is the Institute of Internal Auditors (IIA) and the persons charged with governance (board of directors) to provide internal auditors with clear authority to identify appropriately their roles and responsibilities. From a practical standpoint, internal auditors may re-evaluate their actual roles, and from the various roles that they have undertaken, clarify the confusion that might have occurred concerning their roles. The results provide clear action directives for organisations concerned with the enhancement of the internal audit profession. This paper contributes towards the decision making of boards of directors, audit committees and other regulatory bodies, to augment the profession of internal auditors.